Modeling flame acceleration in H2 turbulent combustion: Strategies to reduce computational cost - A. Dahmani; R.A. Otón-Martínez; F. Nicolás-Pérez; F.J.S. Velasco; O. de Francisco (Results in Engineering)
Reducing the computational cost of fluid dynamics simulations is one of the main challenges in many complex industrial flows’ problems. This challenge becomes more crucial in nuclear safety applications, such as the simulation of accident sequences in large volumes. The present study summarizes the investigations conducted to identify and assess reliable modeling strategies for reducing computational cost for the simulations of hydrogen turbulent combustion in nuclear accident scenarios which consider the flame acceleration, with a primary focus on the use of LES coupled with Artificially Thickened Flame Model (TFM) using a detailed chemical reaction mechanism. For this purpose, the LES-TFM model was benchmarked against experimental data of flame acceleration in a tube for lean mixtures. The obtained results show that LES-TFM model with a detailed 12-reaction chemical kinetics can predict flame acceleration. Moreover, the use of a dynamic grid refinement with an initial coarser mesh with LES-TFM is found to overestimate the time lapse of the initial low-velocity stage of the sequence. However, it permits to simulate the flame acceleration dynamics. Finally, using an effective Lewis of the mixture, adaptive mesh refinement and ISAT are found to be efficient strategies to reduce computational cost with TFM-LES.